IDEOLOGY AS A SOURCE OF LEGAL INNOVATIONS - Ergashev Omonillo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses the relationship between innovation and the ideology of law. Particular attention is paid to the most important innovative tasks of the ideology of law. The analysis of the process of the birth of a new, innovative legal idea is carried out, since the transformation of a new idea into a theory, legal principles and concepts is one of the key points in the process of innovation in law.